Genetic parameters and response to selection in several herds of Iberian pigs for piglets weight at 90 days of age - Ureta P.; Alvarez F.; Dieguez E.; Rodríguez P.; De la Rosa R.S.; Barandiarán M.; García Casco J.M. (7th International Symposium on the Mediterranean Pig, 2012)
The Piglet Index is included in the official genetic scheme for the iberian pig breed, managed since 1992 by the Spanish Association of Iberian Pig Breeders (AECERIBER). This index allows the farmers to select the candidates according with the breeding value for piglet weight at early ages. The data analysed in this work came from 14 breeds with, at least, 1000 piglets controlled in their weight in 10 different seasonal batches. First, heritabilities (h2) and litter effect coefficient (c2) estimates were calculated in each breed using an animal model with fixed and random effects. After, the regression of the average breeding value along time (genetic trend) was estimated also in all 14 breeds. Heritabilities and litter coefficients estimates are quite heterogeneous in their values. So, h2 ranges from 0.00 to 0.24 and c2 from 0.15 to 0.64. In eight breeds h2 reaches values next to zero, results that stress the importance of the quality information (genealogic and productive) provided by the breeder. Genetic trend were positive and significant in eight breeds.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)